Allah's Bomb : The Islamic Quest for Nuclear Weapons - Venter, Al J. (Guilford The Lyons Press, 2007)
Many, including Pakistan, Saudi Arabia, Egypt, and various former Soviet Republics, have been linked to extreme Islamic militant groups. This volume examines the progress of these countries towards nuclear capability, and the repercussions the situation may have on global society.
Include Map, Illustration and Index
Keywords: Nuclear weapons -- Nuclear weapons--Government policy -- Islamic countries -- Diplomatic relations